Communique - Fekete, Albert (4D Journal of Landscape Architecture and Garden Art, 2018)
The Faculty of Landscape Architecture and Urbanism declares 2019 as a centennial memorial year in order for us to notably commemorate two of the faculty’s prominent figures’ 100th birth anniversaries, that of Professor Mihály Mőcsényi and our art teacher András Balogh.
Keywords: Centennial; Mőcsényi; András Balogh